Types of Assessment Tests Used in the Teaching and Learning of English Language in Awendo Sub-County, Kenya - Odundo, Otiep Augustine; Odera, Florence Y.; Oyiengo, Karen A. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2019)
Continuous Assessment is a very important process in any educational program and it is also one of the key steps in curriculum implementation in primary schools in Kenya. The government of Kenya adopted continuous assessment to help in gauging learners’ performance with a view of making necessary adjustments to help improve teaching and learning process. The instructional methodologies used in the teaching and learning process are meant to provide attainment of certain goals in education, however, it can be said that continuous assessment has not been given the attention it requires because learning outcome has continued to be poor, especially in English language in class seven which is a pre-candidate class for national examination. The data on performance of learners in English language as a subject is available in Awendo Sub-County. The purpose of this study was to identify the types of assessment used in teaching and learning of English language in class seven in public primary schools in Awendo Sub-County. Descriptive survey research was used in conducting this study. The study was conducted in Awendo sub-county, Migori County. The study targeted 71 head teachers, 71 class seven teachers of English, 5 Curriculum Support Officers and 2354 pupils, giving a total population of 2501. Saturated sampling was used to sample head teachers, teachers of English and Curriculum Support Officers. However, on the side of the pupils, the researcher used simple random sampling to get the sample size of 235 which is 10% of pupils’ population. Therefore, the total sample size was 382. To establish the validity and reliability of research instruments, piloting was done in two schools that would not be included in the study. Data collection was done using questionnaires for class seven teachers of English and class seven pupils and interview schedules for head teachers and C.S.Os. Data analysis was done through descriptive statistics and results presented in the form of tables, graphs and descriptive form. The findings of this study may be useful to the Ministry of Education officials who are the policy makers, the Teachers Service Commission and other researchers. It may be useful for them to help in undertaking further research in the teaching and assessment of English language in the country. The research findings were as follows: the study revealed that formative assessment was commonly used. The study recommended that the government should employ more teachers to reduce teacher shortages in schools, teachers should use a variety of instructional methods and different types of continuous assessment tests in the teaching and learning. The study also recommended that further research should be done in other counties.